Diastolic Dysfunction in Type 2 Diabetes Mellitus Patients Presenting to Tertiary Care Hospital - Saeed, Hafiz Asad; Abbas, Syed Waqar; Zareen, Syeda Fatima; Hammad, Muhammad; Usman, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To study the frequency of left ventricular diastolic dysfunction in patients with type 2 diabetes mellitus presenting to a tertiary care hospital.Study Design: Cross sectional study.Place and Duration of Study: Medicine Dept, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Mar to Aug 2022.Methodology: Fifty-one patients between the ages of 30 to 65 years were enrolled, belonging to either gender, presenting to outdoor department, with diagnosed type 2 diabetes mellitus for at least 1 year, on oral hypoglycemic drugs or insulin, and no underlying hypertensive cardiac pathology or diastolic dysfunction. These patients were further analyzed using statistical software based on their 2D echocardiogram findings.Results: Out of 51 type 2 diabetes mellitus patients, there were more males 32(62.7%) as compared to females 19(37.3%), with mean age of 52.25±8.09 years. We observed that 21(41.2%) patients did not have left ventricular diastolic dysfunction at the time of our study, but among these patients, 13(61.9%) had type 2 diabetes mellitus for 1-3 years while remaining 30(58.8%) patients had both type 2 diabetes mellitus and left ventricular diastolic dysfunction, with 13(25.5%) having grade-I, 10(19.6%) having grade-II and 7(13.7%) having grade-III categorization.Conclusion: There was an increased risk of left ventricular diastolic dysfunction in type 2 diabetes mellitus with longer duration of disease and higher HbA1c. Patients with type 2 diabetes mellitus to be followed up for diabetic control and monitored for the presence of asymptomatic left ventricular diastolic dysfunction with measures to be taken to prevent it.